Production and Extraction Of Antibacterial Bacteriocin from Pediococcus sp. NWD 015 - N. Nofisulastri; Zaenal Bachruddin; Eni Harmayani (Universitas Gadjah Mada, 2006)
objectives were to study the growth pattern of Pediococcus sp. NWD 015 and bacteriocin activity, extractionand characterization of bacteriocin, and to determine the effect of storage time and temperature on bacteriocinactivity. Results showed that the bacteriocin activity increased during growth and reached the highest activity duringstationary phase. The maximum bacteriocin production reached after incubation of the cell for 12 h at 37oC in TGEbroth and decreased after 96 h incubation. Extraction with adsorbtion-desorbtion method could increased a specificactivity of bacteriocin. Bacteriocin from Pediococcus sp. NWD 015 is inactivated by Proteinase-K; however it is stillactive by heat treatment at 121oC for 15 min and over pH 2 – 11. Bacteriocin of Pediococcus sp. NWD 015 was effectiveagaints Enterococcus faecalis, Staphylococcus aureus, Eschericia coli, Listeria monocytogenes but not against Salmonellathypimurium. The molecular weight of bacteriocin is 4.95 kDa.Keywords : Bacteriocins, Pediococcus sp NWD 015.